2018
DOI: 10.1021/acsanm.8b01060
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Carbonaceous Nanotubes and Mesoporous Nanofibers as Stable Anode Materials for Lithium-Ion Battery

Abstract: The morphologies and pore architectures of carbon nanostructures could be precisely controlled via a selfassembly process. This work presented resorcinol-formaldehyde resin-silica composite nanofibers, which were synthesized through a sol−gel method under the help of costructure directing agent (CSDA) (S)-β-citronellol and nhexanol. The self-assembly process and the nanostructure of obtained composite nanofibers were changed by adding different CSDA. After carbonization and getting rid of silica, carbonaceous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure 2c, the higher ratio of I D /I G in the NPS-XAN (I D /I G ¼ 1.14) sample suggested that high defect structures were obtained through this process and these values are higher than previous reports. [43,44] Raman spectroscopy of C-XAN samples is investigated as shown in Figure S3, Supporting Information. The I D /I G ratio of C-XAN is (I D / I G ¼ 0.6).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2c, the higher ratio of I D /I G in the NPS-XAN (I D /I G ¼ 1.14) sample suggested that high defect structures were obtained through this process and these values are higher than previous reports. [43,44] Raman spectroscopy of C-XAN samples is investigated as shown in Figure S3, Supporting Information. The I D /I G ratio of C-XAN is (I D / I G ¼ 0.6).…”
Section: Resultsmentioning
confidence: 99%
“…The reinforcing effect has also been achieved by filler blending while promoting the dispersion of the filler 26–29 . For example, Pingot et al 30 added different dispersants to CNFs/NBR composites to analyze the reinforcing effect of CNFs on NBR, and the results showed that the addition of dispersants was beneficial to improving the mechanical properties and electrical conductivity of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing effect has also been achieved by filler blending while promoting the dispersion of the filler. [26][27][28][29] For example, Pingot et al 30 added different dispersants to CNFs/NBR composites to analyze the reinforcing effect of CNFs on NBR, and the results showed that the addition of dispersants was beneficial to improving the mechanical properties and electrical conductivity of the composites. Shi et al 31 prepared composites by blending CNTs/CNFs together and found that the blending of carbon materials could mutually promote the dispersion of fillers, which was very helpful in the strengthening the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the nanostructure and preparation of composite materials can effectively inhibit volume expansion, reduce the electrical contact resistance, and improve the electrochemical performance of materials. Associated preparation methods of synthesizing revolutionary nanocomposites include electrospinning [ 29 ], pyrolysis [ 30 ], templating [ 31 ], chemical vapor deposition [ 32 ], sol-gel methods [ 33 ], and so on. A series of Fe 3 O 4 -based nanomaterials were prepared, such as Fe 3 O 4 nanowire arrays [ 34 ], Fe 3 O 4 /graphene composites [ 35 , 36 ], Fe 3 O 4 /carbon nanotube composites [ 37 ], hexahedral Fe 3 O 4 [ 38 ], and hollow Fe 3 O 4 spheres.…”
Section: Introductionmentioning
confidence: 99%